2017
DOI: 10.1080/13557858.2017.1280133
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic newspapers and low-income Spanish-speaking adults: influence of news consumption and health motivation on cancer prevention behaviors

Abstract: Objective: Ethnic newspapers have the potential to reach and influence various cultural and ethnic subpopulations traditionally underserved in the United States. The current study sought to explore how ethnic news consumption interacts with health motivation to predict cancer prevention behaviors in a sample of Spanish-speaking adults. Design: Participants (N = 100) completed a survey in Spanish, with items measuring demographics, acculturation, health literacy, health motivation, ethnic newspaper consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Although we adjusted for factors related to health literacy, such as English language proficiency and education, this finding may reflect differences in other dimensions of health literacy as well as differences in access to and preferences for ethnic print media. Although our study, to our knowledge, is the first nationally representative study to identify ethnic differences in trust of cancer-related information from print media, prior studies have sug-gested that there may be benefits to utilizing ethnic print media to promote cancer prevention behaviors among Hispanics (50,51).…”
Section: Discussionmentioning
confidence: 90%
“…Although we adjusted for factors related to health literacy, such as English language proficiency and education, this finding may reflect differences in other dimensions of health literacy as well as differences in access to and preferences for ethnic print media. Although our study, to our knowledge, is the first nationally representative study to identify ethnic differences in trust of cancer-related information from print media, prior studies have sug-gested that there may be benefits to utilizing ethnic print media to promote cancer prevention behaviors among Hispanics (50,51).…”
Section: Discussionmentioning
confidence: 90%
“…Such distortions have the potential to limit learning from news coverage. However, despite growing literature examining the content of newspaper coverage, there is a lack of research on the effects that such coverage has on news learning (King et al, 2018), especially for ethnic subpopulations (Stryker et al, 2007). Given this, it is important for researchers to continue to unpack the complex relationship between news exposure and news learning, examining processes that may mediate this pathway.…”
Section: Learning From Ethnic News Mediamentioning
confidence: 99%
“…Past work has examined the effects of ethnic news media on the preventive health behaviors of underserved populations, notably low-income, Spanish speaking adults (King et al, 2018). In that study, the authors tested the relationship between consumption of ethnic newspapers and education, acculturation, and adherence to cancer screening behaviors.…”
mentioning
confidence: 99%
“…Thus, it is research-worthy for analyzing and comparing the local media contents published in different languages. Scholars reported that the way the media cover cancer news depends highly on who the target audience is [ 29 ]. Therefore, the focal points of the approach of presenting MI on cancer issues might differ from the local English media and the Chinese media.…”
Section: Introductionmentioning
confidence: 99%